Prácticas políticas identitarias de hombres gay de la Ciudad de México: entre la tensión y la heteronormalización - Lozano-Verduzco, Ignacio (El Colegio de México A.C., 2016)
In this article, the author analyses the discourse of 15 gay men who reside in Mexico City, obtained through in depth interviews, with the objective of understanding how they use their homoerotic desire and sexual identity to carry out political practices. The results show that involvement in gay, feminist, and left-wing activism allows men to undertake processes of political reflection in a more profound manner and be more conscious of their acts. They also show the emotional burden of assuming their homoerotic desire publicly and how this appropiation allows them to question social norms that regulate their desire and identity.